Afraid of the dentist? There's an app for that: Development and usability testing of a cognitive behavior therapy-based mobile app. - Kelly A Daly; Kiara A Diaz-Gutierrez; Armon Beheshtian; Richard E Heyman; Amy M Smith Slep; Mark S Wolff (PLOS Digital Health)
Objectives Although several brief cognitive behavior therapy (CBT)-based treatments for dental fear have proven efficacious, these interventions remain largely unavailable outside of the specialty clinics in which they were developed. Leveraging technology, we sought to increase access to treatment for individuals with dental fear through the development of a mobile application (Dental FearLess). Materials and methods To assess the resonance of our app as an avenue for dental fear treatment, we conducted a study assessing the usability, feasibility, and acceptability of the beta app. Participants with moderate to severe dental fear (N = 80) completed the app and reported on the perceived usability of the mobile interface (Systems Usability Scale, SUS; α = .82) and credibility of the intervention (Credibility and Expectancy Questionnaire, CEQ; α = .88). A sub-sample of participants naïve to the app (n = 10) completed the app during a think-aloud procedure, sharing their candid thoughts and reactions while using the app, prior to reporting on usability and credibility metrics. Results Overall usability (M = 78.5, SD = 17.7) and credibility (M = 21.7, SD = 5.5) of the beta version of the app were good. The think-aloud data further corroborated the app's acceptability, while highlighting several areas for user improvement (i.e., aesthetics, navigation, engagement). Conclusions Usability and acceptability results are promising for the viability of an accessible, feasible, self-administered intervention for dental fear. Refinements made based on user feedback have produced a clinical-trial-ready mobile application. App refinement decisions, informed by user feedback, are representative of the larger literature-that is, of the ubiquitous negotiations m-health developers must make across treatment fidelity, usability, and engagement. Implications for future research are discussed.